Syif’s Doll Smart Model as an Effort to Reduce Status of Debris Index in Elementary School Children - Syifa Yulia Lestari (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background School-age children are a group that is susceptible to dental and oral health problems, the low behavior of maintaining oral hygiene can cause problems with dental health. Factors that influence due to lack of information so the importance of implemented dental health education. The selection of media and methods that are less precise causes the results to be suboptimal, an alternative combination activity that can be used as a health education package is the syif’s doll smart model that provides learning about oral health. Objective To develop syif’s doll smart model as an effort to reduce of status debris index in elementary school children. Methods Research and Development/ (R&D), there are five stages of research namely: information gathering, product/model design, validation expert and revision, product/model trials (quasy experimental with pre test and post test with control group design) and results product/model. The sample was divided into 2 groups, the syif’s doll smart model was an intervention group, dental health education using power points and tooth brushing demonstration in the control group. Data were tested usingtest repeated measure ANOVA, post hoc LCD, independent test. Results Validity expert results showed a p-value of 0.001 which meant that they were relevant as models and modules for dental health education. The score of child indebted debris occurred a significant change p < 0.05 meaning that this model was effective against decreasing the debris status of elementary school children index indicated by p-value of 0.001. Conclusion Syif’s doll smart model is effective as an effort to reduce the status debris index in elementary school children